State-dependent switching control of switched positive fractional-order systems. (May 2016) - Zhao, Xudong; Yin, Yunfei; Zheng, Xiaolong
Abstract: In this paper, the problem of switching stabilization for a class of continuous-time switched positive fractional-order systems is studied by using state-dependent switching. First, the asymptotic stability condition of switched positive fractional-order systems with state-dependent switching is given, which is based on the fractional co-positive Lyapunov method. Moreover, by the sliding sector method, the stability condition of switched positive fractional-order systems whose subsystems are possibly all unstable is obtained. A variable structure (VS) switching law with sliding sector is also proposed to guarantee the switched positive fractional-order system to be asymptotically stable. Finally, two numerical examples are given to demonstrate the advantages and effectiveness of our developed results. Abstract : Highlights: A variable structure control law is proposed for a class of continuous-time switched positive fractional-order systems. The considered systems are possibly composed of all unstable subsystems. The obtained results are based on the fractional co-positive Lyapunov method.